Determinants of Intention in Financial Literacy Buzzering (Study of Central Java Students) - Hamdani, Muliawan; Pantawis, Setyo (Journal of Economic Education, 2023)
Financial literacy is related to individual well-being. Increasing financial literacy is needed to achieve prosperity. Financial literacy education as a way to increase financial literacy is required to utilize technology that can expand networks, including buzz marketing. This research aims to examine the influence of financial literacy, financial attitudes, subjective norms, trust in government and social media technology on the intention to carry out financial literacy buzzing. Analysis using regression shows that trust in the government and social media technology have a significant influence on financial literacy buzzering intentions. Increasing government programs and directing the use of social media technology can be taken to increase financial literacy buzzering intentions.